Pengaruh E-Commerce Terhadap Perilaku Konsumtif Mahasiswa/ Mahasiswi Politeknik STIA LAN Jakarta Program Studi Manajemen SDM Aparatur Angkatan 2022 - Muhammad Naufal Harits Pratama; Dian Indriyani; Sarah Ariza (Journal of Management and Social Sciences, 2024)
The era of Globalization has an impact on the acceleration of technology which affects business transaction media and buying and selling patterns of the community, this encourages people to use business transaction media using the internet in the form of sites and buying and selling application systems or more formally known as e-Commerce and triggers consumptive behavior, especially millennials and Gen Z, but the lack of literature makes a research gap found, namely the Research Evidence Gap. The method used in this research is quantitative by using the SPSS statistical software tool version 27, with a sample of 31 students at Politeknik STIA LAN Jakarta. Data is collected through a questionnaire containing questions about online shopping patterns, ease of access to use and payment on online shopping applications or websites, alternative choices of online shopping applications or websites, online shopping methods, frequency of purchases, factors that influence the emergence of consumptive behavior in students of the Politeknik STIA LAN Jakarta human resource management study program of the apparatus class of 2022. After statistical processing, the result of simple regression analysis is Y = ax + b or Y = 8.516 + 0.429, the T test (Hypothesis), namely T count worth 3.440 is greater than t table worth 2.04523, then H0 is rejected and Ha is accepted, it can be concluded that there is an influence of variable x (the influence of e-Commerce) on variable y (consumptive behavior) and the test of the coefficient of determination (R Square) is 0. 290 This value shows that the influence of the e-Commerce variable on the consumptive behavior of students is 29%, while the rest (71% of student consumptive behavior) is influenced by other variables.